Subarachnoid hemorrhage in a postpartum mother: A rare manifestation of an uncommon disease - Oraianthi Fiste; Evaggelos Mavrothalassitis; Christos Markellos; Alexandros Rodolakis; Flora Zagouri; Meletios-Athanasios Dimopoulos; Michalis Liontos (Elsevier, 2022)
Subarachnoid hemorrhage, a potentially lethal medical emergency, represents an atypical clinical manifestation of gestational choriocarcinoma. We present the uncommon case of a 31-year-old primigravid female who presented with cerebral oncotic aneurysmal rupture, five weeks after vaginal delivery. Albeit the absence of neurological deficits after endovascular embolization, the patient was soon readmitted, complaining of fever, abdominal pain, and fetid lochia, all suggestive of puerperal endometritis. Upon a comprehensive diagnostic work-up, she was subsequently diagnosed with metastatic choriocarcinoma. Early initiation of multiagent chemotherapy, despite being in septic shock associated with Escherichia coli bacteremia, resulted in favorable prognosis.